1977
DOI: 10.1093/ajcp/68.3.368
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Bone Marrow Imprint in the Diagnosis of Leukemic Reticuloendotheliosis (“Hairy Cell Leukemia”)

Abstract: Leukemic reticuloendotheliosis is a distinct entity, often misdiagnosed as chronic lymphocytic leukemia or lymphoma. The neoplastic cells have a specific tartrate-resistant acid phosphatase isoenzyme by which the diagnosis may be secured. Most individuals are leukopenic, and when, as in our case, rare or no circulating cells with tartrate-resistant acid phosphatase activity are found in the peripheral blood, an alternate site must be sought. Bone marrow aspirations often result in "dry taps," however, and cryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The imprinting is a simple methodology, routinely used for diagnostic in other situations, as in the evaluation of sentinel lymph nodes for lobular carcinoma of the breast cancer [36]. Several studies have demonstrated that the imprinting is superior to freezing, particularly in cases where the preservation of the tissue structure is not required [37-40]. Here, we have observed that imprinting provides a higher-quality analysis of a larger number of cells than the cryogenic sectioning and it is an interesting option for screening cell trafficking due to an easily and faster methodology.…”
Section: Discussionmentioning
confidence: 99%
“…The imprinting is a simple methodology, routinely used for diagnostic in other situations, as in the evaluation of sentinel lymph nodes for lobular carcinoma of the breast cancer [36]. Several studies have demonstrated that the imprinting is superior to freezing, particularly in cases where the preservation of the tissue structure is not required [37-40]. Here, we have observed that imprinting provides a higher-quality analysis of a larger number of cells than the cryogenic sectioning and it is an interesting option for screening cell trafficking due to an easily and faster methodology.…”
Section: Discussionmentioning
confidence: 99%
“…The marked and diffuse increase in reticulin fibres (Burke et al, 1974) explains the 'dry tap' that is most often found; however, imprints of marrow biopsies yield adequate diagnostic cytological material (Krause et al, 1977). In the liver, the invasion usually follows the sinusoidal structure, and pseudoangiomatous lesions similar to those of the spleen and lined by hairy cells have also been described.…”
Section: Hairy Cell Leukaemiamentioning
confidence: 99%
“…Touch preparation techniques may vary, but generally involve touching the CNB specimen against a glass slide to create a cytology smear, which is immediately stained and evaluated by a cytotechnologist or cytopathologist, analogous to on-site assessment of FNAs. Most studies on TPs have been based on large-bore breast and bone marrow CNBs, [1][2][3][4][5][6][7][8] and endoscopic gastric mucosal biopsies. [9][10][11][12][13] There have been only a few studies on TPs for CT-guided CNBs, and those studies were focused primarily on the feasibility and the accuracy of cytologic assessment of TPs.…”
mentioning
confidence: 99%